Bricolage in environmental entrepreneurship: How environmental innovators "make do" at the bottom of the pyramid. Issue 4 (21st April 2020) - Musona, Jackson; Sjögrén, Helena; Puumalainen, Kaisu; Syrjä, Pasi
Abstract: Previous studies have discussed extensively the development of business solutions in resource‐constrained environments. However, understanding how local entrepreneurs engaged in environmental innovation can overcome resource constraints at the bottom of the pyramid (BOP) remains an under‐researched area. Under the theoretical framework of bricolage, this study thus adopts a cross‐sector multiple case study approach to provide empirical evidence on how social and environmental entrepreneurs in Kenya design low‐cost solutions to environmental problems and for people at the BOP. The study considers environmental bricolage as a method of innovation ingenuity for social‐environmental entrepreneurs. Network, marketing, waste material, and skills and knowledge bricolage are identified as mechanisms for addressing resource challenges by social and environmental entrepreneurs when creating low‐cost and superior‐value solutions at the BOP. The study further highlights the critical role of boundary‐spanning organizations, the government, external knowledge, and technology.